Effect of Persian and English colour collocations on L2 learners' proficiency - Mahmood Hashemian (Politeknik Negeri Bali, 2019)
Collocations play an important role in L2 teaching and learning. The present study investigated the effect of color collocations in L2 learning. This study was done in 2 phases: In the first phase, the frequency of color collocations was calculated in English and Persian. Two lists of English and Persian color collocations were chosen. Each list included 100 color collocations. The English collocations were chosen from English collocation dictionaries, but the Persian color collocations were chosen by the Persian native speakers. Chi-square results indicated that there were some differences between the 2 languages, but the differences were not statistically significant. In the second phase, the (possible) effect of color collocations on upper-intermediate and advanced L2 learners’ proficiency was investigated. Sixty upper-intermediate and advanced L2 learners, both male and female, were chosen from a private language institute in Isfahan, Iran. The minimum and maximum ages of the participants were about 15-38, and their homogeneity was tested by the OPT. Participants were given a pretest in order to measure their color collocational knowledge. Then, after the treatment, a posttest was administered. Results revealed that teaching collocations had a significant effect on the participants’ proficiency.